Analysis of household electricity consumption behaviours: impact of domestic electricity generation - Motlagh, Omd; Paevere, Phillip; Tang, Sai Hong; Grozev, George (Elsevier, 2015)
Adoption of renewable electricity generation technology such as photovoltaic (PV) systems is at early majority stage in most countries. Depending on solar capacity, applied feed-in tariff, and other factors, households exhibit different electricity consumption behaviours known as demand side management. This article presents three univariate methods to infer deliberative behavioural patterns at households with solar electricity technology. Strategies include qualitative principal component analysis (PCA), unsupervised Hebbian-based clustering, and clustering using a semi-supervised self-organizing map (SOM). The models are individually examined on 300 sample households with rooftop PV panels under gross metering. According to the experiments, the dominant behaviours are often general among most households, and therefore reveal themselves on first and second principal components. However, on the third and forth component the specific behaviours related to load-shifting and self-consumption, are observed. The Hebbian classifier differentiates between at least eight behaviours some of which indicating deliberative behaviours. More effectively, the SOM classifier allows for clear detection of self-consumption behaviour attributed to domestic electricity generation. The experiments, results, discussions, and recommendations for future work are inclusive.